2013
DOI: 10.1614/ipsm-d-12-00058.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biochar on Native and Invasive Prairie Plant Species

Abstract: a carbon-rich product formed by the incomplete combustion of biomass, has been shown to improve soil quality and increase crop growth but has not been evaluated in prairie ecosystems. We assessed the response of a native perennial grass, big bluestem, and an invasive herbaceous perennial, sericea, to biochar amendments in two greenhouse experiments in 2010 and 2011. In the first experiment, big bluestem and sericea were grown in monoculture; the main treatments were soil type (silt, sand), percent biochar (0%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 74 publications
0
25
1
Order By: Relevance
“…For example, biochar (partially burnt plant tissue) and other C supplements may reduce soil N availability by providing C‐rich substrate (Blumenthal, Jordan & Russelle ; Adams et al . ) and some studies suggest that biochar may favour native C 4 grasses (Adams et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, biochar (partially burnt plant tissue) and other C supplements may reduce soil N availability by providing C‐rich substrate (Blumenthal, Jordan & Russelle ; Adams et al . ) and some studies suggest that biochar may favour native C 4 grasses (Adams et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…) and some studies suggest that biochar may favour native C 4 grasses (Adams et al . ). Additionally, strategically timed prescribed burns could reduce forb dominance and increase diversity under increased rainfall variability (Brockway, Gatewood & Paris ; Bowles & Jones ).…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analysis shows that biochar significantly translates to increased crop biomass and plant macronutrients across all soil types and climates (Biederman & Harpole ), but the largest positive influences on plant production have been shown in acidic, nutrient poor soils (Jeffery et al ). In mine substrates, biochar has shown positive effects on native plant growth (Anawar et al ; Roberts et al ), but inconsistent effects on plant biomass (Jones et al ; Adams et al ) Thus, the utility of biochar in restoring plant communities is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its physical properties, BC help increase water holding capacity and reduces nutrient leaching. Biochar is very porous which increases adsorption properties allowing a greater retention of water and nutrients in the soil solution (Adams et al, 2013). One greenhouse study found that the water holding capacity nearly doubled when 15% poultry litter BC by weight was added to 9 kg of sandy loam soil.…”
Section: Introductionmentioning
confidence: 99%